On the Interest Rate Sensitivity of Aggregate Investment in the Euro Zone - Reichel, Richard (Asian Journal of Economic Modelling, 2022)
The purpose of this paper is to estimate the response of aggregate investment to interest rate changes in the Euro zone. Keynesian macroeconomic theory assumes that there is an inverse relationship between investment and interest rates, but empirical evidence is inconclusive. Interestingly, there are no studies relating macroeconomic investment to central bank rates in the Euro zone, despite the importance of this question for European monetary policy. To check whether the inverse interest rate – investment nexus holds for the Euro zone we conducted a comprehensive econometric study. In particular, we estimated a modified accelerator model that related aggregate investment in levels and the investment-to GDP (gross domestic product) ratio to income, interest rates and a set of control variables. The model was estimated by OLS (ordinary least squares) and simultaneous-equations methods such as TSLS (two-stage least squares) and GMM (generalized method of moments). The study was unable to uncover a significant interest rate effect on investment in the Euro zone. Thus, there is little support for the expansionary monetary policy of the European Central Bank.